Be Wise in Social Media - Irfandi Samosir; Sherly Ester Elaine Kawengian (SANCTUM DOMINE: JURNAL TEOLOGI, 2022)
Social media is a platform of collective interaction and communication with an internet connection. Various data says that youth and adolescents are the largest group of social media users. Many problems arise due to the neglect of healthy communication principles. This research aims to examine the principles and aspects of communication that need to be considered based on a textual study of James 3:1-12. The research method used is descriptive qualitative with an exposition approach and hermeneutic principles in interpreting the text and referring to various literatures related to the subject of the study. The findings in the study show that healthy communication on social media must pay attention to social, personal, and spiritual aspects.